Mythology in first nations art of the Northwest Coast - Vítová, Jana (2007)
The thesis examines art of the Northwest Coast First Nations in the context of mythology. It covers such issues as materials and technologies used, basic artistic styles, and motifs and their symbolism. It also tries to prove the importance of art in the life of the Northwest Coast Native peoples.